Cell-Free Supernatant of Odoribacter splanchnicus Isolated From Human Feces Exhibits Anti-colorectal Cancer Activity - Oh, Byeong Seob; Choi, Won Jung; Kim, Ji-Sun; Ryu, Seoung Woo; Yu, Seung Yeob; Lee, Jung-Sook; Park, Seung-Hwan; Kang, Se Won; Lee, Jiyoung; Jung, Won Yong; Kim, Young-Min; Jeong, Jae-Ho; et al. (Frontiers in Microbiology, 2021)
The gut microbiota (GM) has been shown to be closely associated with the development of colorectal cancer (CRC). However, the involvement of GM is CRC has mainly been demonstrated by metagenomic profiling studies showing the compositional difference between the GM of healthy individuals and that of CRC patients and not by directly studying isolated gut microbes. Thus, to discover novel gut microbes involved in CRC, we isolated the GM from the feces of healthy individuals and evaluated its anti-CRC activity in vitro and in vivo. After GM isolation, cell-free supernatants (CFSs) were prepared from the isolated gut microorganisms to efficiently screen a large amount of the GM for anti-proliferative ability in vitro. Our results showed that the CFSs of 21 GM isolates had anti-proliferative activity against human colon cancer HCT 116 cells. Of these 21 GM isolates, GM07 was chosen for additional study because it had the highest anti-cancer activity against mouse colon cancer CT 26 cells in vitro and was further evaluated in a CT 26 allograft mouse model in vivo. GM07 was identified as Odoribacter splanchnicus through phylogenetic analysis based on 16S rRNA gene sequencing. Further investigation determined that the CFS of O. splanchnicus (OsCFS) induced anti-proliferative activity via apoptosis, but not cell-cycle arrest. Moreover, GC/MS analysis suggested that the putative active molecule in OsCFS is malic acid. Finally, in the CRC mouse model, peri-tumoral injection of OsCFS significantly decreased CRC formation, compared to the control group. Altogether, these findings will provide valuable information for the discovery of potential probiotic candidates that inhibit CRC.